2007
DOI: 10.1177/159101990701300304
|View full text |Cite
|
Sign up to set email alerts
|

Disappearing Saccular Intracranial Aneurysms: Do They Really Disappear?

Abstract: Evolution and natural history of cerebral aneurysms is a dynamic process. Spontaneous regression in size or complete disappearance of an aneurysm is a known phenomenon, more commonly noted in giant intracranial aneurysms. However, reappearance or regrowth of such aneurysms is rare with few anecdotal reports. We report a series of four cases including one giant aneurysm, which either disappeared or regressed on sequential angiograms. Regrowth or reappearance of two of these previously disappeared or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…8 Furthermore, non-ionic contrast media not only have a pro-coagulant effect but also tend to have a higher propensity for thrombosis. 5 Another publication supports the fact that endothelial injury due to turbulent flow leads to increased platelet deposition, platelet aggregation and thrombus formation. 9 On the other hand, reviewed literature shows the association between hormonal factors and VAD.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…8 Furthermore, non-ionic contrast media not only have a pro-coagulant effect but also tend to have a higher propensity for thrombosis. 5 Another publication supports the fact that endothelial injury due to turbulent flow leads to increased platelet deposition, platelet aggregation and thrombus formation. 9 On the other hand, reviewed literature shows the association between hormonal factors and VAD.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, various hemodynamic factors such as slow and turbulent blood flow resulting from blood stasis due to increased intracranial pressure or induced hypotension seem to have an important role in thrombosis of both small and large aneurysms. 5,6,7 Spetzler et al has shown the use of anti-fibrinolytic agents as ''spontaneous cure'' for a previously thrombosed aneurysm although it resulted in a short-term effect. 8 Furthermore, non-ionic contrast media not only have a pro-coagulant effect but also tend to have a higher propensity for thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“… 14) Although the pathophysiology of spontaneous recanalization has not been fully elucidated, recanalization ensuing from complete thrombosis of aneurysms has been reported in many studies. 4) 5) 11) 12) 16) 19) 21) 22) In these studies, recanalization of acute thrombosis of the aneurysm was observed in the days and weeks after thrombosis. Therefore, follow-up angiogram and careful observation during the follow-up period are required for fear of recanalization resulting in rebleeding of the aneurysm.…”
Section: Discussionmentioning
confidence: 90%
“…Several mechanisms and dynamic parameters related to spontaneous thrombosis of intracranial aneurysms have been suggested 10) ; including 1) stasis of blood in the aneurysm sac, 2) a ratio of aneurysm sac volume to orifice area than 28:1 (mm 3 :mm 2 ), 3) stagnation of blood in a large aneurysm, 4) endothelial injury due to turbulent blood flow, and 5) stasis of contrast material in the aneurysm sac. Hamilton and Dold proposed that hypotension, severe vasospasm, use of antifibrinolytic agents, giant aneurysm, and local injury to the arterial wall were associated with spontaneous obliteration of aneurysm in the ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%